The Desert Edge: Flora of the Guaymas–Yaqui Region of Sonora, Mexico - Press, BRIT (Journal of the Botanical Research Institute of Texas, 2023)
From the publisher: This magnificent flora of the Sonoran Desert’s southern edge represents decades of meticulous work and the genius of Richard Felger (1934–2020) and his colleagues at their best. It is many things at once. A project of passion that was sparked by a trip in 1953 by an impressionable young scientist whose world was opened by canyons lined with palms, fig trees, agaves, and plants awaiting his description. The most thorough treatment of the plants of the southern half of the Sonoran Desert ever assembled, which fills a long-standing gap in the knowledge of Mexican Biodiversity. A flora brought to life by hundreds of vivid and beautiful images of the majority of the 837 plant taxa found here, most by Sue Carnahan, who brought this life-spanning project to realization with Richard and Jesus. And a flora made approachable through accurate diagnostic keys (as Richard says, “the poetry of botany”), tailored to this specific region over years in the canyons and along the coasts and countless hours at the herbarium refining measurements and decoding a floristic jumble into an orchestrated whole.